Preferences Regarding Self-Management Intervention Outcomes of Dutch Chronically Ill Patients With Limited Health Literacy - van der Gaag, Marieke; Heijmans, Monique; Ballester, Marta; Orrego, Carola; Niño de Guzmán, Ena; Ninov, Lyudmil; Rademakers, Jany (Frontiers in Public Health, 2022)
Abstract Background For many chronically ill patients self-management of their disease is difficult. This may be especially true for people with limited health literacy as they are faced with additional challenges in the day-to-day management of their disease. Research has shown that self-management support is most effective when tailored to the needs and preferences of patients. Therefore, this study explores the preferences regarding self-management outcomes of chronically ill patients with limited health literacy. Methods A total of 35 patients with limited health literacy were invited to a concept-mapping procedure consisting of two card sorting tasks. Patients ranked 60 outcomes, which are often found in literature in relation to self-management, to the level that was important for themselves. Means were calculated for each outcome and domain, and differences within the group were analyzed. Results For patients with limited health literacy, satisfaction with care is the most important outcome domain. This domain includes overall satisfaction, the communication with health care providers, the provision of information and trust. At an outcome level, outcomes related to symptom management and improving competences to self-management scored very high. No differences between patient groups for age and sex were found. Conclusion Chronically ill patients with limited health literacy prefer a wide variety of outcomes for their self-management. Next to health related outcomes, patients mostly prefer to work on their competences for self-management. For health care professionals, acting on these patient preferences and building a solid relationship will enhance successful self-management.